2016
DOI: 10.1093/mnras/stw3253
|View full text |Cite
|
Sign up to set email alerts
|

Precise clustering and density evolution of redMaPPer galaxy clusters versus MXXL simulation

Abstract: We construct a large, redshift complete sample of distant galaxy clusters by correlating Sloan Digital Sky Survey (SDSS) Data Release 12 (DR12) redshifts with clusters identified with the red-sequence Matched-filter Probabilistic Percolation (redMaPPer) algorithm. Our spectroscopic completeness is > 97% for ≃ 7000 clusters within the redMaPPer selection limit, z 0.325, so that our cluster correlation functions are much more precise than earlier work and not suppressed by uncertain photometric redshifts. We der… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 125 publications
(164 reference statements)
3
32
0
Order By: Relevance
“…In the velocity unit, the amplitude of the signal is from 5 to 2 km/s depending on the samples. This is consistent with previous results [9,10,12]. The result also shows that the amplitude of the signal decreases from left to right in Table III.…”
Section: Satellite Galaxies Virialised In Halossupporting
confidence: 93%
See 1 more Smart Citation
“…In the velocity unit, the amplitude of the signal is from 5 to 2 km/s depending on the samples. This is consistent with previous results [9,10,12]. The result also shows that the amplitude of the signal decreases from left to right in Table III.…”
Section: Satellite Galaxies Virialised In Halossupporting
confidence: 93%
“…This demonstrates that the gravitational redshift is potentially an interesting test of modified gravity [10]. However, the random velocity of central galaxies could be a systematic error [9,10,12]. When the central galaxy has a random velocity dispersion of 30% of the satellite galaxies, the prediction changes, as shown in Table V.…”
Section: Satellite Galaxies Virialised In Halosmentioning
confidence: 99%
“…Using these observable quantities as mass proxies on the one hand and the connection between cluster masses and their bias on the other, we can make inference on the cosmological model. Most attempts to follow this route have resulted in cosmological parameters that disagree with the constraints obtained using the number counts of the same sample (Schuecker et al 2002), however, or lead to strongly disagreeing scaling relations (Jimeno et al 2017). Remarkably, Allevato et al (2012) obtained a precise agreement between the modeling of the clustering based on the weak-lensing mass calibration and the measured clustering amplitudes of galaxy groups by taking the definition of the object and the effects of sample variance into account.…”
Section: Introductionmentioning
confidence: 99%
“…These works are extensions of precise modeling of galaxy distributions to include higher order effects of redshift-space distortions and other effects. The gravitational redshift and the second order Doppler effect (from the second order peculiar velocity) in the galaxy clusters are one of such topics [22][23][24][25][26][27]. Measurements of the gravitational redshift with galaxies associated with clusters have been reported [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The gravitational redshift and the second order Doppler effect (from the second order peculiar velocity) in the galaxy clusters are one of such topics [22][23][24][25][26][27]. Measurements of the gravitational redshift with galaxies associated with clusters have been reported [22][23][24]. It is worth mentioning that recent research indicated that the gravitational redshift caused by the local gravitational potential may become a source of bias in the calibration of cosmological parameters using type Ia supernovae data combined with other cosmological probes, provided that we have no prior knowledge about the local gravitational potential [28].…”
Section: Introductionmentioning
confidence: 99%